2020
DOI: 10.1136/bmjopen-2020-040427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermittent preventive treatment for malaria with dihydroartemisinin-piperaquine on immune responses to vaccines among rural Ugandan adolescents: randomised controlled trial protocol B for the ‘POPulation differences in VACcine responses’ (POPVAC) programme

Abstract: IntroductionDrivers of lower vaccine efficacy and impaired vaccine-specific immune responses in low-income versus high-income countries, and in rural compared with urban settings, are not fully elucidated. Repeated exposure to and immunomodulation by parasite infections may be important. We focus on Plasmodium falciparum malaria, aiming to determine whether there are reversible effects of malaria infection on vaccine responses.Methods and analysisWe have designed a randomised, double-blind, placebo-controlled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Data and samples from ongoing and completed trials will be used to explore mechanisms and identify biomarkers of adverse biological status with respect to vaccine responses. In Uganda, three POPVAC trials are investigating the effects of rural versus urban location, and Schistosoma mansoni and malaria exposure and treatment, on responses to live parenteral (BCG, Yellow Fever), live oral (Typhoid [Ty21a]), Human Papilloma Virus (HPV) and toxoid (tetanus/diphtheria) vaccines; and the effect of BCG revaccination on response to other vaccines [27][28][29][30] . Results are expected in 2023, and samples will be available for investigation.…”
Section: Wp 1 Biosciencementioning
confidence: 99%
“…Data and samples from ongoing and completed trials will be used to explore mechanisms and identify biomarkers of adverse biological status with respect to vaccine responses. In Uganda, three POPVAC trials are investigating the effects of rural versus urban location, and Schistosoma mansoni and malaria exposure and treatment, on responses to live parenteral (BCG, Yellow Fever), live oral (Typhoid [Ty21a]), Human Papilloma Virus (HPV) and toxoid (tetanus/diphtheria) vaccines; and the effect of BCG revaccination on response to other vaccines [27][28][29][30] . Results are expected in 2023, and samples will be available for investigation.…”
Section: Wp 1 Biosciencementioning
confidence: 99%
“…Malaria is a highly prevalent disease in settings where poor responses to unrelated vaccines has been reported to occur (Natukunda, 2020). Several studies have shown that Plasmodium infection might impair vaccine induced protective immunity against other pathogens (Dietz et al, 1997;Cunnington and Riley, 2010).…”
Section: Protozoan Parasites and Vaccines Against Bacterial Pathogensmentioning
confidence: 99%